Modern aspects of hepatology: liver steatosis and fibrosis through the prism of comorbidity in pediatric practice - Strashok, Larysa; Turchyna, Svetlana; Shevchenko, Natalia; Yeloyeva, Zalina; Belousova, Olga; Tsodikova, Olha (ScienceRise: Medical Science, 2021)
The relevance of the topic is dictated by the growing prevalence of hepatic steatosis and fibrosis in the pediatric population, which is due to an increase in the number of pathologies of various organs and systems, which may be accompanied by the development of these liver lesions. The aim of the study: to analyze the data of modern sources of scientific literature regarding the prevalence and features of the course of pathology of various organs and systems, which is associated with the development of steatosis and liver fibrosis in the pediatric population. Materials and methods. A systematic search of scientific was carried out using Web of Science, Scopus, PubMed, scientific bases with key words: «hepatic steatosis», «hepatic fibrosis», «non-alcoholic fatty liver disease», «comorbid pathology», «children and adolescents». Conclusions. Currently, the number of children and adolescents who are diagnosed with steatosis and/or fibrosis of the liver is increasing in the world. In particular, the formation of this pathology is associated with the presence of metabolic syndrome and is associated with its main components, such as obesity, hypertension, disorders of carbohydrate and lipid metabolism. More and more studies indicate the role of non-alcoholic fatty liver disease, which is based on steatosis, as a comorbid pathology in systemic, cardiovascular, endocrine diseases, gastrointestinal tract pathology, and genetic disorders. Also, a number of drugs with steatogenic and fibrogenic effects on liver tissue have been established, which are widely used in pediatric practice. It is necessary to monitor the structural and functional state of the liver already in childhood and adolescence for adequate treatment of the underlying disease and prevention of the formation of comorbid pathology